New early jurassic U-Pb age in rhyolitic dykes from the northeastern sector of gastre (Chubut, Argentina) and its possible relation to the mineralization of the los manantiales district - Lagorio, Silvia L. (2018)
Fil: Lagorio, Silvia L. Instituto de Geología y Recursos Minerales (IGRM). Servicio Geológico Minero Argentino. Buenos Aires, Argentina.